MULTIFUNCTION IS NOT ENOUGH AN APROACH TO A NEW CONCEPT IN URBAN SPACE LE TERROIR - Rainha, Ana Paula Parreira Correia; Ogando, Francisco Ferreira de Lima Araújo (European Scientific Journal, ESJ, 2015)
The idea is to analyse two urban spaces located close together (Chiado and Carmo), in order to evaluate the differences between them, namely: why is it that before two urban spaces of multifunctional characteristics the touristic impact can be so diverse? The answer is almost spontaneous: the heritage in all its forms - historic, cultural, architectonic, literary, artistic… etc. These variables are, undoubtedly, meaningful, but still there is more to it. This is where the terroir concept comes in. Usually applied in vitiviniculture, it defines in a gestalt way the territory, distinguishing the wine from one place to another. The concept itself summarizes something that often cannot be explained: for instance, why do two wines produced in territories with seemingly the same characteristics achieve unequal success? Besides the controllable elements/factors, other interactions arise which surpass the controllable and contribute to the presence of a unique taste. With the territory/urban space the same thing happens, there are elements that interact with each other changing the whole: it’s the terroir!